Dissimilar Joining by Explosive Welding: Aluminium to Copper and Aluminium to Steel - Carvalho, Gustavo Henrique Senna de Freitas Ligeiro de (2019)
Doctoral Thesis in Mechanical Engineering, in the field of Production Technologies submitted to the Faculty of Sciences and Technology of the University of Coimbra